Impact of women’s participation on village savings and loan on children’s nutritional diversity in rural Chimanimani in Zimbabwe - Kudakwashe A. Mbiro; Thabo Ndlovu (Jàmbá, 2021)
The prevalence of malnutrition in children below the age of 5 years in rural Zimbabwe, resulting from low income and the inability to meet food and medical expenses, marks huge disparities between rich and poor households. Efforts to improve child health and nutrition status culminated in different strategies being employed, chief amongst them is the enhancement of access to financial capital for vulnerable communities through improved women participation in village savings and loan (VSL). The study sought to examine the influence of women’s participation in VSL and its impact on child health and nutrition in rural Chimanimani. Arnstein’s Ladder of Participation and the United Nations Children’s Fund’s (UNICEF) framework anchor discussions on the participation of women, VSL financial resources usage by women, contribution of VSL to food diversity for children and ultimately to food consumption patterns before and during women’s participation in VSL. The study was largely qualitative and explored the descriptive research design to collect data by using semi-structured questionnaires and in-depth interviews. The findings show that the majority of participants used funds from VSL to purchase food, invest in income-generating activities and finance medical expenses. Village savings and loan contribute to an increase in food consumption score and meal dietary diversity for children, and at the same time it improved child care, health and nutrition in the rural Shinja community. The study concluded that genuine participation of women in VSL positively influenced the improvement in children’s health and nutritional diversity and that the VSL model is a multifaceted tool, which can be intertwined with other interventions to contribute to the attainment of the sustainable development goals.